2009
DOI: 10.1210/jc.2008-1402
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Respiratory Failure and Mild Primary Hypothyroidism in a Term Girl with a de Novo Heterozygous Mutation in the TITF1/NKX2.1 Gene

Abstract: This is the first reported case of a heterozygous TITF1/NKX2.1 mutation leading to neonatal death from respiratory failure. The association of severe unexplained respiratory distress in a term neonate with mild primary hypothyroidism is the clue that led to the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 31 publications
4
37
1
1
Order By: Relevance
“…A few normal-sized follicles with cuboidal epithelium and intense nuclear NKX2-1 staining were interspersed between slightly enlarged to extremely dilated, multilobulated follicles with a flattened epithelium and thyrocytes exhibiting non-NKX2-1 nuclear staining. In the only other paper describing thyroid histology in a patient with an NKX2-1 mutation, no abnormalities were found [Maquet et al, 2009]. In contrast, the histological alterations found in our patient were very similar to those described in adult mice of the thyroid follicular cell-specific conditional KO mouse line Nkx2-1(fl/fl);TPO-Cre [Kusakabe et al, 2006], which suggested that NKX2-1 was required to maintain the normal architecture and function of the differentiated thyroid gland.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A few normal-sized follicles with cuboidal epithelium and intense nuclear NKX2-1 staining were interspersed between slightly enlarged to extremely dilated, multilobulated follicles with a flattened epithelium and thyrocytes exhibiting non-NKX2-1 nuclear staining. In the only other paper describing thyroid histology in a patient with an NKX2-1 mutation, no abnormalities were found [Maquet et al, 2009]. In contrast, the histological alterations found in our patient were very similar to those described in adult mice of the thyroid follicular cell-specific conditional KO mouse line Nkx2-1(fl/fl);TPO-Cre [Kusakabe et al, 2006], which suggested that NKX2-1 was required to maintain the normal architecture and function of the differentiated thyroid gland.…”
Section: Discussionsupporting
confidence: 76%
“…Few detailed descriptions are available in the literature. The case of an infant with lethal respiratory failure and an I207F NKX2-1 mutation was reported recently [Maquet et al, 2009]. In our two patients, severe neonatal respiratory distress evolving to ILD was the most prominent manifestation of the triad, similar to the picture observed in surfactant protein disorders.…”
Section: Discussionsupporting
confidence: 74%
“…In a recent series that also reviewed the clinical and pathologic findings of 46 patients with TTF-1 deficiency, pulmonary disease occurred in 54%, with ''infant respiratory distress syndrome'' being the most common (7). The pulmonary pathology has been described briefly in one patient, whereas only one other case report illustrates the pathologic findings (10,11).…”
mentioning
confidence: 99%
“…У экспериментальных мышей с нулевой мутацией NKX2-1 были зарегистрированы легочные дефекты, включающие аномальную альвеоляризацию, локальное утолщение альвеолярных перегородок, гипертрофию альвеолоцитов II типа, снижение синтеза сурфактанта [24][25][26]. По некоторым данным, у пациентов с мутацией NKX2-1 и легочной манифестацией заболевания высока вероятность летального исхода (16-24%) [12,23].…”
Section: клиническая характеристика и диагностикаunclassified